2018
DOI: 10.1038/s41433-018-0151-y
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity in the United Kingdom: retreatment rates, visual and structural 1-year outcomes

Abstract: Retreatment rates are in line with previous reports, and appear higher after initial anti-VEGF antibody than after initial diode laser. Refractive outcomes are in line with previous studies, with a trend towards early emmetropia and myopia following diode laser, particularly in more severe ROP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
2
8
0
1
Order By: Relevance
“…A Swedish ROP register (SWEDROP) with a coverage of 97% (Holmstr€ om et al, 2019), however, reveals a high recurrence rate (26%) in infants treated with laser only during the years 2008-2012(Holmstr€ om et al, 2016, remaining the same also during the years 2013-2017(Holmstr€ om et al, 2019. The Swedish retreatment frequency is high as compared to the ETROP Study (13.9%) and a recent British Study (11%) (Adams et al, 2018). Furthermore, the SWEDROP study investigated the experience of the lasertreating surgeon (Holmstr€ om et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A Swedish ROP register (SWEDROP) with a coverage of 97% (Holmstr€ om et al, 2019), however, reveals a high recurrence rate (26%) in infants treated with laser only during the years 2008-2012(Holmstr€ om et al, 2016, remaining the same also during the years 2013-2017(Holmstr€ om et al, 2019. The Swedish retreatment frequency is high as compared to the ETROP Study (13.9%) and a recent British Study (11%) (Adams et al, 2018). Furthermore, the SWEDROP study investigated the experience of the lasertreating surgeon (Holmstr€ om et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Lower recurrence rates have been reported in cohorts comprising infants born with a wider range of GA. 22 It is well known that recurrence is more common after anti-VEGF injections than after laser treatment. [23][24][25] In the Rainbow trial, which formed the basis for approving the anti-VEGF drug ranibizumab for ROP, treatment recurrence rates were 18.9% after laser treatment and 31.1% after ranibizumab treatment. 11 The high recurrence rate after anti-VEGF in our study may be partly due to the high percentage (5.5%) of infants with APROP, the most aggressive form of ROP with high risk for recurrence after treatment.…”
Section: Centre and Treatment Modalitymentioning
confidence: 99%
“…Based on the reported refractive outcomes, we divided the studies into four categories: 1) those that revealed a lower rate of refractive error in the anti-VEGF treated eyes [20][21][22]; 2) those that revealed no significant difference in refractive outcomes between the two treatment modalities [9,16,23]; 3) those that revealed a higher rate of refractive error in the anti-VEGF treated eyes [24] or compared refractive outcomes between two anti-VEGF agents [25][26][27]; and 4) those that reported refractive outcome of sequential treatment with laser after initial anti-VEGF treatment [28,29]. Table 1 summarizes the refractive outcomes reported in the 33 primary studies.…”
Section: Resultsmentioning
confidence: 99%
“…The third category consisted of seven papers, including 481 eyes of 337 premature infants, comparing refraction outcomes of anti-VEGF and laser treatments [24], bevacizumab and ranibizumab [25][26][27]31], or reported refraction outcomes of bevacizumab monotherapy [32,33] (Table 1). Despite low levels of myopia in the anti-VEGF-treated eyes, refractive outcomes differed with the anti-VEGF agent, with the eyes treated with bevacizumab being significantly more myopic [25,26].…”
Section: Resultsmentioning
confidence: 99%